Etika Pengelolaan Pemerintahan Perspektif Hukum Islam - Ilham Ramadhan; Nurul Hadist; Kurniati Kurniati (Ethics and Law Journal: Business and Notary, 2024)
Government ethics in Islam provides a strong moral foundation for the administration of a modern state. This research examines the ethical principles of Islamic government and their relevance in modern times. Through qualitative analysis of the Al-Quran, Hadith, and related literature, this research identifies three main pillars: honesty as a manifestation of trust, integrity in acting, and deliberation as a decision-making mechanism. The results show that applying these principles can increase transparency, accountability and public participation in government. Although there are challenges such as westernization and corruption, technological advances and democratization open new opportunities to make this happen. This research contributes to understanding the influence of Islamic values on ethical and effective governance practices, while providing valuable information to policy makers, practitioners and academics about building good and sustainable governance. AbstrakEtika pemerintahan dalam Islam memberikan landasan moral yang kuat bagi penyelenggaraan negara modern. Penelitian ini mengkaji prinsip-prinsip etika pemerintahan Islam dan relevansinya di zaman modern. Melalui analisis kualitatif terhadap Al-Quran, Hadits, dan literatur terkait, penelitian ini mengidentifikasi tiga pilar utama: kejujuran sebagai manifestasi amanah, integritas dalam bertindak, dan musyawarah sebagai mekanisme pengambilan keputusan. Hasilnya menunjukkan bahwa penerapan prinsip-prinsip tersebut dapat meningkatkan transparansi, akuntabilitas, dan partisipasi masyarakat dalam pemerintahan. Meskipun terdapat tantangan seperti westernisasi dan korupsi, kemajuan teknologi dan demokratisasi membuka peluang baru untuk mewujudkannya. penelitian ini berkontribusi untuk memahami pengaruh nilai-nilai Islam terhadap praktik tata kelola yang etis dan efektif, sekaligus memberikan informasi berharga kepada pembuat kebijakan, praktisi, dan akademisi tentang membangun tata kelola yang baik dan berkelanjutan.